Thermal Analysis of Insulation Materials Used for Exterior Walls of Buildings Considering the Wind Effect - Uçar, Aynur (Hibetullah KILIÇ, 2022)
The optimum thickness of insulation material dependent on wall orientation and wind speed were determined for selected insulation materials and external wall types in different compositions and orientations by using the Life Cycle Cost method. The methodology is applied as a case study by comparing the different combinations of thermally insulated walls with four different insulation materials for four different degree-day regions of Turkey considering the effect of wind speed and direction. In the economic analysis, the costs of the life cycle of each different combination of insulated walls were calculated. It was obtained from these results that heating requirement of the north facing wall was the highest and heating requirement of the south facing wall was the lowest. The optimum thickness of insulation changes from 4.77 to 13.35 cm dependent on the insulation materials and orientations.
Keywords: Mechanical Engineering; Makine Mühendisliği